EVALUATION OF CLINICAL, DEMOGRAPHIC AND ELECTROENCEPHALOGRAPHY FINDINGS OF DRAVET SYNDROME PATIENTS - Mahmut Aslan; Serdal Güngör (İstanbul Tıp Fakültesi Dergisi)
Objective: Dravet syndrome (DS) is a severe myoclonic epilepsy affecting infants and is classified among epileptic syndromes. Generally, the first seizures begin with febrile diseases during infancy. Cognitive functions and behavior of patients begin to decline from the age of two. In DS, the most common SCN1A mutation is detected. Material and Method: The study included 18 patients with DS who were presented to Inonu University Pediatric Neurology Clinic between 2012 and 2017. We retrospectively evaluated the demographic characteristics, seizure frequency, AED therapies and response to treatment. Results: The mean age of our patients was 4.22±2.12 years. The F/M ratio was 1.57. The age of onset of seizures was 6.7±2.9 months. 77% of damage affecting patients was febrile onset. 77.7% of our patients were from VPA; 66.6% of the patients benefited from BZD, and sodium voltage-gated channel alpha subunit 1 (SCN1A) mutation was detected in all of our patients. Two patients were monozygous twins and three siblings were also monozygous. The same mutation was observed in our sister patients who were monozygous and their age at seizure onset, seizure type, clinical course, and responses to AEDs were similar. The same mutation was observed in three siblings, but the age at the time of seizure, the onset of seizures, the seizure type, clinical course, and response to AEDs were different from each other. Conclusion: If neuromotor developmental retardation is associated with recurrent febrile seizures, DS should be considered among the preliminary diagnoses. Instead of this sentence, the most common cause of Dravet syndrome among these patients is the SCN1A mutation.